Self-Assembled Peptide Nanoarchitectures: Applications and Future Aspects - Prakash Sharma, Prem; Rathi, Brijesh; Rodrigues, Joao; Yu. Gorobets, Nikolay (Current Topics in Medicinal Chemistry, 2015)
Among the diversity of natural and synthetic compounds being studied and applied for human welfare, peptides able to develop nanostructures are currently under special attention of scientists. In this review, we focus on such properties of peptides and various kinds of intramolecular interactions allowing their ability to form different shapes of nanoassemblies. We have also discussed the applications of self-assembled peptides in various biomedical fields where they can be employed as cargo to target delivery of drugs, genes, in tissue engineering, regenerative medicines, and biosensors.
Keywords: Peptide nanoube